Biotechnological potential of salicornias in Ecuador: a review of agricultural establishment and therapeutic properties - Naranjo-Moran, Jaime (2025)
The objective of the review was to analyze the feasibility of the productive establishment of salicorn species in Ecuador, with the aim of contributing to the bioprospecting of plants of food and pharmaceutical interest. Salicornias contain bioactive compounds such as phenols, sterols and unsaturated fatty acids, which confer them significant therapeutic properties, including diuretic, depurative, anti-osteoporotic, anticancer and antihyperglycemic effects. In addition, although interaction with beneficial microorganisms is limited, it can improve the growth and resistance of salicornias under high salinity conditions. In conclusion, the agro-productive establishment of salicornias in Ecuador is feasible and sustainable, offering opportunities for research in the food, pharmaceutical, agricultural and environmental industries, contributing to the development of rural communities through the creation of beneficial bioproducts for consumers.